Peran Indonesia Dalam Memerangi Terorisme - Reni Windiani (Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Since the terrorist attacks of September 11th 2001 in World Trade Centre (WTC), terrorism becomes a hot issue trough out the world. Almost all states agree to counter terrorism, because terrorism is against humanitarianism, and it has caused losses in economy, politics, and psychology.This research is aimed to describe and analyze Indonesia’s multi pronged approach to counter terrorism by using qualitative research method. Based on the data and information provided could be concluded that Indonesia’s role in countering terrorism is seen through three aspects, Government has made a legal frame work on anti-terrorism, form an institution which focus on cooperate with ASEAN. Meanwhile in international level, Indonesia has signed an agreement made by the United Nation, and cooperated with other non-ASEAN countries.Based on the result of this research, researcher’s suggestions for strengthening Indonesia counter terrorism efforts over the next decade are: intensifying coordination and communication between the central government and local government in the domestic level in order to implement what has been written in the legal framework. In the regional level, ASEAN needs to increase cooperation related to information and defense. Lastly, in the international level, there